Analisis Pemahaman Konsep Biologi Menggunakan Pilihan Ganda Beralasan Dalam Materi Pokok Sel Pada Siswa Kelas XI IPA SMA Negeri 1 Dampal Selatan. The Analysis of Conceptual Understanding in Biology Subject by Using Multiple Reasoned Choice on Cell Topic - sagap, sagap; N. Husain, M.P, Sarjan; Djirimu, Muchlis (Universitas Tadulako, 2014)
Abstract This research was conducted at SMAN 1 Dampal Selatan in 2013, the objective of this research was to analyze the students understanding in Biology concept by using multiple reasoned choice on cell topic. This research used descriptive method. The subject of this research was the 39 student of class XI IPA at SMAN 1 Dampal selatan. This research was begin by preparing the test in the form of multiple reasoned choice. The total numbers of the questions were 20. Those questions were selected based on the indicators which had to be achieved by the students in accordance to the standart competence and basic competence in KTSP curriculum. Those questions were also need to be declared valid by the validator of the test who was also the biology Teacher in that school. The analysis result on the students understanding in biology concept particularly in cell topic showed that there were 26,79% of the students understood about the materials, 28,72% of the students still confused about the materials and the rest 44,49% of the students could not understand the concept of cell topic at all. These results were collected by the use of multiple reasoned choice test form. Â Keyword : Analysis, Conceptual Understanding, and Multiple Reason Choice. Â Abstrak Penelitian ini dilaksanakan di SMA Negeri 1 Dampal Selatan Tahun 2013, bertujuan untuk menganalisis pemahaman konsep biologi siswa menggunakan pilihan ganda beralasan pada materi pokok sel. Penelitian ini menggunakan metode deskriptif dengan subjek penelitian yaitu siswa SMA Negeri 1 Dampal Selatan kelas XI IPA yang berjumlah 39 siswa. Penelitian ini diawali dengan penyusunan soal pilihan ganda beralasan sebanyak 20 soal yang disusun berdasarkan indikator yang harus dicapai oleh peserta didik sesuai dengan Standar Kompetensi dan Kompetensi Dasar pada Kurikulum Tingkat Satuan Pendidikan atau KTSP dan dinyatakan valid oleh Validator. Hasil analisis pemahaman konsep siswa terhadap materi pokok sel menunjukkan bahwa sebanyak 26,79% paham, 28,72% miskonsepsi dan 44,49% tidak paham terhadap konsep materi pokok sel yang diujikan dengan menggunakan bentuk tes pilihan ganda beralasan. Kata Kunci : Analisis, Pemahaman Konsep, dan Pilihan Ganda Beralasan.